A New Preclinical Model of Retinitis Pigmentosa Due to Pde6g Deficiency - Jentzsch, Michelle Carmen; Tsang, Stephen H.; Koch, Susanne Friederike (Ophthalmology science (Online), 2023)
Retinitis pigmentosa (RP) is the most common cause of inherited blindness, with onset occurring as early as 4 years of age in certain rare but severe forms caused by mutations in the gamma subunit of phosphodiesterase 6 (PDE6). Studies in humans and mice have shown that RP pathology begins with progressive photoreceptor death, which then drives changes in downstream neurons, neighboring retinal pigment epithelium (RPE), and vasculature. Here, we present the first detailed analysis of RP disease progression in Pde6g-deficient mice. Experimental study of an RP mouse model. We studied Pde6g−/− and Pde6g+/− mice at the age of 7, 16, 30, 44, and 56 days with n = 2 to 5 per group and time point. Photoreceptor degeneration and retinal remodeling were analyzed in retinal sections by immunofluorescence. Retinal blood vessel degradation was analyzed in flat-mounted retinas immunolabeled for isolectin GS-IB4. Protein expression was measured by immunoblot. Acellular capillaries were assessed in trypsin-digested and hematoxylin–eosin-stained retinas at postnatal day (P) 44. Retinal pigment epithelium cells were delineated in flat-mounted RPE-choroid-sclera by immunolabeling for the cell-adhesion protein β-catenin. Immunofluorescence and morphometry (quantitative analysis of outer nuclear layer, dendrite area, vessel area, acellular vessels, RPE cell size, number of nuclei per RPE cell, RPE cell eccentricity, and RPE cell solidity). This novel RP model exhibits early onset and rapid rod degeneration, with the vast majority gone by P16. This pathology leads to retinal remodeling, including changes of inner retinal neurons, early activation of glia cells, degradation of retinal vasculature, and structural abnormalities of the RPE. The pathology in our Pde6g−/− mouse model precisely mirrors human RP progression. The results demonstrate the significant role of the gamma subunit in maintaining phosphodiesterase activity and provide new insights into the disease progression due to Pde6g deficiency. Proprietary or commercial disclosure may be found after the references.